Comparison of the Effectiveness of Dialectical Behavior Therapy Skills Training (DBT-ST) and Mindfulness-Based Cognitive Therapy (MBCT) on Cognitive Emotion Regulation in Individuals with Symptoms of Borderline Personality Disorder - Samadi, Bahareh; Mirzaian, Bahram; Ghanadzadegan, Hossein Ali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Borderline Personality Disorder (BPD) is the most common personality disorder in psychiatric settings and one of the disorders that causes the most harm to individuals. The aim of the present study was to compare the effectiveness of Dialectical Behavior Therapy Skills Training (DBT-ST) and Mindfulness-Based Cognitive Therapy (MBCT) on cognitive emotion regulation in individuals with symptoms of Borderline Personality Disorder. Methods and Materials: This research was a semi-experimental study, utilizing a pre-test, post-test design with a control group and a follow-up period. The statistical population included all clients aged 18 to 45 who referred to counseling centers in the city of Sari during the first half of 2022 and had files. From all these individuals, those willing to cooperate were selected through purposive non-random sampling, resulting in a sample of 45 participants. These individuals were then randomly assigned to three groups (Group 1: Dialectical Behavior Therapy Skills Training, n = 15; Group 2: Mindfulness-Based Cognitive Therapy, n = 15; and Group 3: Control group, n = 15). Data collection was conducted using the Cognitive Emotion Regulation Questionnaire by Garnefski et al. (2001). The Dialectical Behavior Therapy Skills Training group (2003) participated in 12 weekly 90-minute group sessions, and the Mindfulness-Based Cognitive Therapy group (2002) participated in 8 weekly 90-minute group sessions. Data were analyzed using repeated measures ANOVA. Findings: The results indicated that Dialectical Behavior Therapy Skills Training and Mindfulness-Based Cognitive Therapy were effective on cognitive emotion regulation in individuals with symptoms of Borderline Personality Disorder (P = 0.001). There was a significant difference in the effectiveness of Dialectical Behavior Therapy Skills Training and Mindfulness-Based Cognitive Therapy on cognitive emotion regulation between the experimental groups and the control group. Conclusion: Based on the results of this study, it can be concluded that Dialectical Behavior Therapy Skills Training and Mindfulness-Based Cognitive Therapy, through individuals’ cognitive coping strategies, can lead to improvements in psychological indicators and enhancement of mental health in individuals with symptoms of Borderline Personality Disorder.